Contemporary majority nationalism - Gagnon, Alain; Nootens, Geneviève; Lecours, André, 1972- (Studies in nationalism and ethnic conflict, 2011)
"For many years nationalism has been associated with political demands by minority nations that challenge the rights of the central state. However, over the last two decades many works have challenged this perspective, arguing that nationalism - as a political phenomenon - is likely to emerge among both majority and minority nations. In light of a renewed interest in the study of nationalism, Contemporary Majority Nationalism brings together a group of major scholars committed to making sense of this widespread phenomenon. To better illustrate the reality of majority nationalism and the way it has been expressed, authors combine analytical and comparative perspectives. In the first section, contributors highlight the paradox of majority nationalism and the ways in which collective identities become national identities. The second section offers in-depth case study analyses of France, the United Kingdom, Spain, Canada, and the United States. This book is an international project led by three members of the Research Group on Plurinational Societies based at Université du Québec à Montréal. " --Publisher's website.